RUSSIA AND GUAM - SKAKOV, Alexander (CENTRAL ASIA AND THE CAUCASUS, 2008)
It would seem expedient to discuss the topic “Russia and GUAM” in the context of the integration unions existing in the post-Soviet space, that is, with respect to the CIS and, to some extent, its alternative organizations. It is very evident that the activity of the CIS, despite the obvious need, in our opinion, for its further existence, at least as a negotiation platform, does not fully meet the functions of an integration structure. There are many different reasons for this, such as the Common-wealth’s diversity and the ineptness of its bureaucratic machinery, as well as the outmoded ambitions and phobias that are prevalent in some cases. So, it was inevitable that integration organizations emerged that posed as alternatives to the CIS and singled out a few of the stronger nuclei within the Commonwealth. It is another matter that this demand could be and was used by external forces interested in forming all kinds of counterbalances to Russia or simply in weakening Russia as the CIS’s only driving force due to its potential. At the same time, Russia’s rather bumpy relations with some of the Commonwealth states prompted the latter to step up their participation in these alternative structures. Subsequently, normalization of the relations between the Russian Federation and any given CIS country led, as a rule, to the withdrawal of that state from the alternative integration union. It is worth noting that Uzbekistan, which joined GUAM in 1999, left it in May 2005 after its relations with Russia cardinally improved. Moldova, which has essentially curtailed its participation in GUAM due the normalization of relations between Chisinau and Moscow, is currently heading in the same direction.Correspondingly, the Russian factor has a way of exerting very tangible pressure both on the emergence and on the further existence of alternative unions. So, the vision we offer of the GUAM’s past, and present will be based on our understanding of Moscow’s viewpoint on this issue, as well as on Russia’s national interests.